Featural Identity and the Obligatory Contour Principle: Perspective from the Sound Pattern of Standard British English and Nigerian English - Utulu, Don Chukwuemeka (European Scientific Journal, ESJ, 2022)
Yip (1988) shows that, in English, the insertion of /ɪ/ between coronal sibilants, e.g., /s/ and /z/ in plural nouns like /fɒksɪz/ foxes, /tæksɪz/ taxes, etc. and the prohibition of geminate stress, as in *thirˈteen ˈmen is motivated by the Obligatory Contour Principle (OCP). She argues that /ɪ/-epenthesis and geminate stress avoidance are triggered in the language to satisfy the OCP, which prohibits adjacent identical elements in phonological representation. In this study, we show that the OCP also explains why: (i) English inserts /ɪ/ between coronal sibilants in genitive forms, ruling out */rəʊz(z) pɜ:s/ ‘Rose’s purse’, (ii) the language drops yod after post-alveolars, /ʧ/, /ʤ/ and /ʃ/, ruling out */ʧju/, ‘chew’, */ʤju/ ‘Jew’, and (iii) it disallows heteromorphemic geminate consonants, e.g., /t # t/ by making them undergo fusion, /t/. This study investigates the extent of applying these native English OCP-motivated rules in Nigerian English (NigE) based on the data gathered from fifty educated NigE speakers. Results of the frequency count and constraint-ranking in this study showed that the OCP-based native English rules in NigE could be inviolable (56.48%) or violable (43.52%). We argue that the frequency of NigE violation of the OCP is in part determined by the complex nature of the sequential combinations of English identical features and the NigE speakers’ level of competence in English usage.